Heaven on earth / Nur Husna Serip Mohamad - Serip Mohamad, Nur Husna (Academy of Language Studies, 2023)
Switzerland is a country famous for its natural beauty. Thus, it is really not misleading to call it heaven on earth! It is definitely one of the most suitable countries to visit during holidays. Personally, I love to visit Switzerland during Winter. In fact, I have been to Switzerland twice to enjoy the snow with my friends and family. With my friends, we explored Zurich, Interlaken, Lauterbrunnen, Grindelwald, Lucerne, Berne and Zermatt. However, I had to skip Zermatt while travelling with my family due to the distance, and since my brother sprained his ankle, a few days before our Europe trip. In both trips, walking around Grindelwald and Interlaken with Christmas decorations and ginger breads gives me a feeling of walking in a Fairy tale land, where Santa and the elves hide.